ANALISIS KALIMAT TANYA PADA PERCAKAPAN DALAM NOVEL “ PRIDE AND PREJUDICE” KARYA JANE AUSTEN - sri arfani fani (LPPM Universitas Bina Sarana Informatika, 2016)
This research belongs to a study on translation. It deals with a work to search the accuracy of the translating of question words sentences from English into Indonesian. The study was aimed (1) to describe the translating of kinds of question words sentences in” Pride and prejudice novel by Jane Austen” and (2) to suggest some alternative renderings for the inappropriate ones.The method of the research was descriptive in nature. The data were collected from an English novel and its Indonesian translation, using observation-documentation method. The total number of the data was 50 question words sentences. The data analysis was conducted by the use of the method of intra lingual matching.The result of the data analysis showed that among 40 sentences of all kinds of question words sentence that appear from page 4-70( from chapter 1- chapter 16), 40 sentences of question words of them were appropriately translated, and only 10 sentences of question words of them were inappropriately rendered in Indonesian. Finally, it can also be concluded that the question sentence equivalent analysis of the conversation in the Pride and Prejudice Novels are categorized as a translation which has high equivalent degree. Translation will has high equivalent if translator understand not only concern about how to translate from SL to TLbut also must notice about the language aspects.Keywords: analysis, question words sentences, Novel.Penelitian ini termasuk dalam penelitian terjemahan. Penelitian ini berkaitan dengan sebuah karya untuk mencari keakuratan menerjemahkan kata-kata pertanyaan dalam kalimat dari bahasa Inggris ke bahasa indonesia. Penelitian ini bertujuan untuk: 1) Mendeskripsikan jenis kalimat pertanyaan yang diterjemahkan dalam